The Effects of Chronic Asprosin Administration on Sense of Smell and Sexual Behavior in Female Rats - Oz, Zeynep Dila; Kacar, Emine; Serhatlioglu, Ihsan; Ozdede, Mehmet Ridvan; Atila, Busra; Horoz, Mert Ali; Kelestimur, Haluk (Karger, 2023)
IntroductionAsprosin is an adipokine released from white adipose tissue during fasting and acts through the olfactory receptor. It is known that adipokines play roles in reproductive physiology in mammals. However, there are very few studies conducted on role of asprosin in reproductive functions. There are no studies on its relationship with sexual motivation. It was shown in the literature that administration of asprosin to male mice improves olfaction. It is also known that there is a strong correlation between smell and sexual desire. In view of this, it was hypothesized that chronic administration of asprosin would improve olfactory performance and increase sexual incentive motivation in female rats for male partners. MethodsThis hypothesis was tested by applying the hidden cookie test, sexual incentive test, active research test, and sexual behavior test. The changes in serum hormone levels in female rats that chronically received asprosin were also measured and compared. ResultsChronic asprosin exposure increased olfactory performance, male preference ratio, male investigation preference ratio, activity index, and anogenital investigation behavior. Also, serum oxytocin and estradiol levels increased following chronic administration of asprosin in female rats.Discussion/ConclusionThese data suggest that chronic administration of asprosin can result in increased sexual incentive motivation for opposite-sex in female rats over increased olfactory performance and changes in reproductive hormones.
Keywords: Mammalian Social Odors; Hormonal Predictors; Partner Preference; Motivation; Oxytocin; Dysfunction; Leptin; Roles; Neuropeptides; Recognition